Hydro-geomorphological research in earth sciences: A systematic review of literature - Kaushalendra Prakash Goswami; Himanshu Shekher (National Geographical Journal of India, 2022)
Water is the most important geomorphic agent for geomorphological action. Hydro-geomorphology is a sub-field of geomorphology that provides a scientific description of the evolution of landforms. The former deals with the study of the spatial interaction of water with the earth’s surface. The introduction and implementation of new techniques make descriptions more useful and informative. Remote sensing and GIS provide highly dynamic space through which assessment and analysis of these geomorphic forms become feasible. The application of hydro-geomorphological study is most useful in management and planning. The present paper focuses on a systematic review of literature on geomorphology, hydro-geomorphology, and mapping, and explains how sub-discipline such as fluvial geomorphology is different from hydro- geomorphological.